2017
DOI: 10.1037/tps0000103
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism in the real world: How proficiency, emotion, and personality in a second language impact communication in clinical and legal settings.

Abstract: The field of psycholinguistics has long documented how communicating in a second language (L2) can be more challenging than communicating in a first language (L1) because of factors such as low L2 proficiency, accent, and L1 versus L2 differences in the appreciation of semantic or pragmatic nuance (e.g., the emotional connotations or words). Moreover, given that language performance is a primary medium through which people both express their personality and evaluate the personality characteristics of others, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 88 publications
1
22
0
1
Order By: Relevance
“…How could the observed difficulties of the patients with poor language concordance be explained and what might cause them? The connotation of words in the native and second language, especially those related to emotions, has been reported to differ among bilingual individuals [25]. Our findings demonstrated that this phenomenon also concerns culturally homologous and substantially bilingual minorities unquoted in any previous studies.…”
Section: Discussionsupporting
confidence: 53%
“…How could the observed difficulties of the patients with poor language concordance be explained and what might cause them? The connotation of words in the native and second language, especially those related to emotions, has been reported to differ among bilingual individuals [25]. Our findings demonstrated that this phenomenon also concerns culturally homologous and substantially bilingual minorities unquoted in any previous studies.…”
Section: Discussionsupporting
confidence: 53%
“…An equally intriguing question, which forms the topic of this paper, is whether word emotionality encountered in one's first language (L1) has a different impact on cognitive and linguistic processing compared to one's second language (L2), and if so, why. Here, the literature is somewhat less developed, though an emerging consensus is that emotional word processing is less intense for L2 compared to L1 language (reviewed in Itzhak, Vingron, Baum & Titone, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of language and its impact in working therapeutically with clients from CaLD backgrounds has been recognised for decades, both in the United Kingdom (Bager-Charleson, Dewaele, Costa, & Kasap, 2017;Bowker & Richards, 2004;Costa, 2010;Gulina & Dobrolioubova, 2018;Itzhak, Vingron, Baum, & Titone, 2017;de Zulueta, 1990) and the United States (Burck, 2004;Hodes, 1989;Marcos, 1976;Santiago-Rivera, 1995;Santiago-Rivera & Altarriba, 2002;Santiago-Rivera et al, 2009). Despite the frequency of bilingual and multilingual families presenting for therapy, limited research has addressed issues related to differences in language between therapist and the family, and there is less about the implications of family members speaking two or more languages, the major themes identified being: 'listening and understanding the client'; 'interventions and interpretations'; 'potential impact of language on the therapeutic encounter: therapist's point of view'; and 'therapist's experience of self' (Gulina & Dobrolioubova, 2018).…”
Section: Impact Of Bilingualism and Multilingualism In Therapymentioning
confidence: 99%